Korelasi Informasi Nilai Gizi terhadap Keputusan Pembelian Biskuit dan Kukis oleh Konsumen Jakarta dan Sekitarnya - I Kadek Putra Yudha Prawira; C Hanny Wijaya; Endang Prangdimurti (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
A healthy diet can be done when the nutritional composition in the product consumed is known clearly. Today, information regarding nutrients composition in processed food products are avai-lable on the food label, particularly the nutrition fact. However, when the information is not used pro-perly, then healthy diet also can not be done properly and may impact on health conditions. Unfortu-nately, information regarding how often consumers Jakarta and the surrounding areas read the nutrition fact is still unknown yet. Moreover, whether the correlation between reading frequency on nutrition fact label and purchase decisions of biscuit-cookie products is also unknown. This study was conducted to determine those correlations. The data were collected through an online survey upon 424 respondents in Jakarta and the surrounding areas. The result showed that the reading frequency on nutrition fact label was positively correlated to the purchase decision of biscuit-cookie products (Pearson correlation 0.447), which is mean the more often read the nutrition fact tend to take the decision in purchasing bis-cuit-cookies products. However respondents were still more concern in the price and sensory charac-teristics (taste, texture, aroma, etc.) of biscuit-cookies instead of the composition and nutrition fact.